Let Expressions

In our use of the word let thus far, we've been making definitions in the toplevel and in .ml files. For example,

# let x = 42;;
val x : int = 42

defines x to be 42, after which we can use x in future definitions at the toplevel. We'll call this use of let a let definition.

There's another use of let which is as an expression:

# let x = 42 in x+1
- : int = 43

Here we're binding a value to the name x then using that binding inside another expression, x+1. We'll call this use of let a let expression. Since it's an expression it evaluates to a value. That's different than definitions, which themselves do not evaluate to any value. You can see that if you try putting a let definition in place of where an expression is expected:

# (let x = 42) + 1
Error: Syntax error: operator expected.

Syntactically, a let definition is not permitted on the left-hand side of the + operator, because a value is needed there, and definitions do not evaluate to values. On the other hand, a let expression would work fine:

# (let x = 42 in x) + 1
- : int = 43

Another way to understand let definitions at the toplevel is that they are like let expression where we just haven't provided the body expression yet. Implicitly, that body expression is whatever else we type in the future. For example,

# let a = "big";;
# let b = "red";;
# let c = a^b;;
# ...

is understand by OCaml in the same way as

let a = "big" in
let b = "red" in
let c = a^b in

That latter series of let bindings is idiomatically how several variables can be bound inside a given block of code.


let x = e1 in e2

As usual, x is an identifier. We call e1 the binding expression, because it's what's being bound to x; and we call e2 the body expression, because that's the body of code in which the binding will be in scope.

Dynamic semantics.

To evaluate let x = e1 in e2:

  • Evaluate e1 to a value v1.

  • Substitute v1 for x in e2, yielding a new expression e2'.

  • Evaluate e2' to a value v2.

  • The result of evaluating the let expression is v2.

Here's an example:

    let x = 1+4 in x*3
-->   (evaluate e1 to a value v1)
    let x = 5 in x*3
-->   (substitute v1 for x in e2, yielding e2')
-->   (evaluate e2' to v2)
      (result of evaluation is v2)

Static semantics.

  • If e1:t1 and if under the assumption that x:t1 it holds that e2:t2, then (let x = e1 in e2) : t2.

We use the parentheses above just for clarity. As usual, the compiler's type inferencer determines what the type of the variable is, or the programmer could explicitly annotate it with this syntax:

let x : t = e1 in e2

results matching ""

    No results matching ""